Analysis of Maslahah mursalah on the Problem of Absentee Land Ownership in Gresik Regency - Al Hafiz, Si Yusuf; Harry, Musleh (al-Rasῑkh: Jurnal Hukum Islam, 2026)
Although Government Regulation Number 41 of 1964 explicitly prohibits absentee land ownership, the practice of agricultural land control by owners domiciled outside the sub-district remains prevalent, particularly in Gresik Regency. This study aims to analyze the factors contributing to the persistence of absentee land practices in Wonosari Hamlet, Banyuurip Village, and to review its implications from the Maslahah mursalah perspective. This research employs a juridical-empirical method with a sociology of law approach. Data were obtained through field observations and in-depth interviews with landowners, village officials, and the National Land Agency (BPN). The results indicate that the dominant factors driving absentee ownership are economic investment motives by urban residents (Surabaya) and weak land administration supervision at the village and sub-district levels. From the Maslahah mursalah perspective, this practice contradicts the principle of public interest as it undermines the preservation of wealth (hifz al-mal) and life (hifz al-nafs) of the local community. The abandonment of productive land deprives local tenant farmers of economic access, triggering unemployment and agrarian structural inequality. Therefore, a revitalization of the local government’s role in enforcing land redistribution sanctions is necessary to achieve substantive agrarian justice.